Analisis Dasar Hukum dan Penerapan Standar Pelayanan Minimal (SPM) dalam Penyelenggaraan Pelayanan Publik - Sri Yuliyanti Mozin; Regina Alfanesya Machmud; Regina Rahmadani Ismail; Nurul Rabiatul Adawiyah; Ralda Ivanka A Labino (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Abstract This study aims to analyze the legal basis and mechanisms for implementing Minimum Service Standards (MSS) in public service delivery in Indonesia. As a strategic instrument, the MSS is designed to ensure the fulfillment of citizens' constitutional rights through quality basic services. Using qualitative research methods with a juridical-normative approach, this study evaluates the extent to which the implementation of the MSS has been able to create equitable access to services and identifies crucial factors influencing its success. The results indicate that although the MSS has a solid legal basis through Law No. 23 of 2014 and Government Regulation No. 2 of 2018, the reality on the ground still shows significant gaps. Implementation of this policy is often hampered by low organizational capacity at the regional level, limited human resource (HR) competency, inaccurate sectoral data, and weak inter-institutional coordination. This study concludes that the effectiveness of the MSS is highly dependent on strengthening regional fiscal capacity, political commitment of leadership, and the integration of valid data-based planning. This is necessary to achieve social justice and equitable welfare within the framework of a welfare state in Indonesia.